EFFICIENCY OF PLOWING SYSTEMS ON WEEDS DENSITY AND GROWTH IN BARE FALLOW UNDER DRY LAND FARMING IN NORTHERN IRAQ - A.M. Sultan (Mesopotamia Journal of Agriculture)
Weed control study on bare fallow was conducted during growing season 2008/2009 at field of Agricultural College,Mosul University to determine the efficiency of two plowing ( disk plow,chisel plow and without plowing),time of plowing (winter,winter + spring,spring) and duration time for weed samples taken from the field (1st April,14th April,11 May)on narrow or broadleaf weed control in dry land farming.Result indicated that there is high density of weeds/m2 in untreated plowing up to137.1 . Disk plow gave the best treatment for weed control which reached up 96.8% when compared with chisel plow 65.5%. related to unplowing treatment.Disk plow was reduced numbers,dry weight and moisture content in weeds. Also plowing at winter + spring gave agood weed control when compard with other treatments while duration time for weed sampls which had been taken from different treatments were unsignificant . Disk plow showed suppriority in weed control when was used at different time of plowing (winter,winter + spring,spring) which gave efficiency in weed control until 11 May.Therefor, it is desirable to use disk plow in winter + spring or in spring to get 100% weed control of narrow or broadleave from beginning to mid April.